Lymphocyte chromosome breakage in low benzene exposure among Indonesian workers (Medical Journal of Indonesia, 2014)
Background: Benzene has been used in industry since long time and its level in environment should be controled. Although environmental benzene level has been controlled to less than 1 ppm, negative effect of benzene exposure is still observed, such as chromosome breakage. This study aimed to know the prevalence of lymphocyte chromosome breakage and the influencing factors among workers in low level benzene exposure. Methods: This was a cross sectional study in oil & gas industry T, conducted between September 2007 and April 2010. The study subjects consisted of 115 workers from production section and head office. Data on type of work, duration of benzene exposure, and antioxidant consumption were collected by interview as well as observation of working process. Lymphocyte chromosome breakage was examined by banding method. Analysis of relationship between chromosome breakage and risk factors was performed by chi-square and odd ratio, whereas the role of determinant risk factors was analyzed by multivariate forward stepwise. Results: Overall lymphocyte chromosome breakage was experieced by 72 out of 115 subjects (62.61%). The prevalence among workers at production section was 68.9%, while among administration workers was 40% (p > 0.05). Low antioxidant intake increases the risk of chromosome breakage (p = 0.035; ORadjusted = 2.90; 95%CI 1.08-7.78). Other influencing factors are: type of work (p = 0,10; ORcrude = 3.32; 95% CI 1.33-8.3) and chronic benzene exposure at workplace (p = 0.014; ORcrude = 2.61; 95% CI 1.2-5.67), while the work practice-behavior decreases the lymphocyte chromosome breakage (p = 0.007; ORadjusted = 0.30; 95% CI 0.15-0.76). Conclusion: The prevalence of lymphocyte chromosome breakage in the environment with low benzene exposure is quite high especially in production workers. Chronic benzene exposure in the workplace, type of work, and low antioxidant consumption is related to lymphocyte chromosome breakage. Thus, benzene in the workplace should be controlled to less than 1 ppm, and the habit of high antioxidant consumption is recommended.